Primary treatment of advanced non-small-cell lung cancer: role of monoclonal antibodies. (October 2012) - de Melo Gagliato, Débora; Shimada, Andrea K; Jardim, Denis Leonardo; Katz, Artur
SUMMARY  Metastatic non-small-cell lung cancer (NSCLC) is one of the most incident cancers for which no curative therapies exist. New insights into the genetic background of the disease have led to the development of new effective therapies, including monoclonal antibodies. Bevacizumab demonstrated improved response rate and progression-free survival in two Phase III trials in association with conventional chemotherapy as first-line treatment for metastatic NSCLC. Cetuximab has proved to be effective in patients with advanced NSCLC expressing EGFR by immunohistochemistry. One of the promising targets in NSCLC is the MET pathway, for which monoclonal antibodies are under development. This review aims to describe the role of monoclonal antibodies for advanced NSCLC and future perspectives in this field.